Individual differences in gaze-cuing effect are associated with facial emotion recognition and social conformity - Shin, Won-Gyo; Park, Hyoju; Kim, Sung-Phil; Sul, Sunhae (Frontiers in Psychology, 2023)
Spontaneous gaze following and the concomitant joint attention enable us to share representations of the world with others, which forms a foundation of a broad range of social cognitive processes. Although this form of social orienting has long been suggested as a critical starting point for the development of social and communicative behavior, there is limited evidence directly linking it to higher-level social cognitive processes among healthy adults.Here, using a gaze-cuing paradigm, we examined whether individual differences in gaze following tendency predict higher-order social cognition and behavior among healthy adults.We found that individuals who showed greater gaze-cuing effect performed better in recognizing others' emotion and had greater tendency to conform with group opinion. These findings provide empirical evidence supporting the fundamental role of low-level socioattentional processes in human sociality.